2016
DOI: 10.1002/2016gl067897
|View full text |Cite
|
Sign up to set email alerts
|

Earth's ion upflow associated with polar cap patches: Global and in situ observations

Abstract: We report simultaneous global monitoring of a patch of ionization and in situ observation of ion upflow at the center of the polar cap region during a geomagnetic storm. Our observations indicate strong fluxes of upwelling O+ ions originating from frictional heating produced by rapid antisunward flow of the plasma patch. The statistical results from the crossings of the central polar cap region by Defense Meteorological Satellite Program F16–F18 from 2010 to 2013 confirm that the field‐aligned flow can turn up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…As the convection speed increases, upflows may be seen when the electron temperature is not elevated above the ion temperature. These observations were assigned to frictional heating described previously by Zhang et al (2016), which only occur when the plasma convection speed exceeds 1,000 m/s. Many more upflow events associated with plasma patches occur when the electron temperature exceeds the ion temperature.…”
Section: 1029/2018gl079099mentioning
confidence: 53%
See 2 more Smart Citations
“…As the convection speed increases, upflows may be seen when the electron temperature is not elevated above the ion temperature. These observations were assigned to frictional heating described previously by Zhang et al (2016), which only occur when the plasma convection speed exceeds 1,000 m/s. Many more upflow events associated with plasma patches occur when the electron temperature exceeds the ion temperature.…”
Section: 1029/2018gl079099mentioning
confidence: 53%
“…As the T i / T e ratio or the T i ‐ T e difference increases, which implies that the patches are turning from hot patches to classical patches, the vertical flux turns from upward to downward. The vertical flux also increases with the increasing convection speed, which corresponds to frictional heating and patch evolution (Ma et al, ; Zhang et al, ) and localized field‐aligned current associated with electron heating (Strangeway et al, ). When T i / T e = 0.8, or T e = T i + 600 K, we see a transition between upward and downward flux in the DMSP data set.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeh and Foster [] reported a supersonic ion outflow speed at 800 km altitude during a great storm event with a maximum K p of 9, and a speed of 400–500 m/s at 400 to 500 km altitude. Zhang et al [] also indicated the correlation between the horizontal ion drift and the vertical ion drift at the DMSP satellite altitude in the polar cap, suggesting effects of frictinal heating. In addition to frictional heating effects, the study also suggested that localized heating produced by precipitating O + could account for observed ion outflows.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang QH et al (2016a) reported simultaneous global monitoring of a patch of ionization and in situ observations of ion upflow at the center of the polar cap region during a geomagnetic storm. These observations indicate strong fluxes of upwelling O + ions originating from frictional heating produced by rapid antisunward flows of the plasma patch.…”
Section: Ionospheric Irregularity and Scintillationmentioning
confidence: 99%